The development and study of immersed burning apparatus with multiple phases inversion - Никольский, Валерий Евгеньевич (Technology audit and production reserves, 2015)
The results of researches the phenomenon of multiple phase inversion for ascending gas-liquid flow in immersed burning apparatus (IBA) is given in the article. For the first time it is shown that the organization of multiple inversions of gas-liquid contacting phases in the direct-flow gas-liquid by heightwise installation of separation grids or valve plates intensifies heat and mass transfer and favorably distinguishes them from bubbling devices of similar purpose. This ensures high efficiency of contact phases; stable operation over a wide load range gas and liquid; high transporting property of liquids by gas, which simplifies heating technology; high intensity of processes in the gas – liquid system; reducing fuel consumption for heating the coolant (or technological product).